The Influence of Electronic Medical Record Toward Drug Planning Quality at the Pharmacy Department of the Hospital ‘X’ - Hendrawati, Menik; Agushybana, Farid; Kartini, Apoina (Public Health Perspective Journal, 2021)
Since 2016, the Hospital ‘X’ has been operating an Electric Medical Record (EMR) and it is integrated with all units, including pharmacy, and it intends to increase its efficiency. 50% of hospital’s income comes from the pharmacy and there is no evaluation related to the using of EMR towards quality of drugs planning. The purpose of this research is to know the correlation between technology factors (system quality, information quality, service quality) of EMR and quality of drugs management at the pharmacy of the Hospital ‘X’. This research uses quantitative research method with cross-sectional approach, and it involves 53 respondents with questionnaire as the data collection technique. The data itself analyzed by SEM PLS (Structural Equation Model-Partial Least Square). The research results show that the information quality of EMR gave significant correlation with the quality of drugs planning, whereas the system quality and EMR service quality were not influenced. The correlation between the information quality and the perception of drugs management quality was significant with T-statistics 7,9508>1.96 and the sample original value was 0.6551. The system quality was not significant with T-statistics 1.6159 < 1.96 and the sample original value was positive, 0.1702. The service quality was not significant with T-statistics 0.6297 < 1.96, with the sample original value was negative, -0.0591. This research shows that the simplicity aspect in understanding the information influences towards the utilization of drugs management, but it needs to increase the system and service quality from the devices, connectivity, network, and upgrading the staff capability aspects.